The basis and effects of the division between private and public law in classical ıslamic law - (:unkn) unknown (My University, 2014)
Batı hukuk kültüründe kendisine yaygın olarak atıf yapılan Kamu Hukuku ve Özel Hukuk ayrımı, hukuku iki farklı alana ayırmaktadır. Özellikle Hanefi doktrini tarafından geliştirilen Kul hakkı - Allah hakkı ayırımının İslam hukukunda benzer bir fonksiyonu olduğunu ve bu ayrıma paralel görülebileceğini söyleyebiliriz. Kul hakkı belirli fertlerin inhisar ve ihtisasları altındaki hakları, temel olarak da medeni hukuk terimiyle paralel olan “muamelat” alanındaki yetkileri ve kısas gibi bazı ceza konularını kapsar. Allah hakkı ise belirli kişilerin inhisarı ve ihtisası altında olmayıp kamunun tamamını ilgilendiren, onların yararını içeren haklardır. Özellikle had cezaları ve diğer kamusal hususlar ise Allah hakkı alanına girmektedir. İslam hukukçuları fıkhın bu iki alanını bazı temel kriterler bakımından birbirinden ayırmışlardır. Kul hakkı/Özel hukuk alanının, kulların inhisar ve ihtisasını belirten en önemli terim olan, “milk” kavramı etrafında şekillendiğini ve nikah ve kısastaki hakların da bu terim etrafında açıklandığını görürüz. Ayrıca fıkhın özel hukuka çok daha geniş bir yer ve zaman ayırdığını, fıkhın ana teorilerini hep özel hukuk alanında geliştirdiğini söyleyebiliriz.

The distinction between public law and private law is commonly referred to in Western legal culture and is considered as the basis of the classification of law. When we study whether such a distinction exists in Islamic law, we discover that it particularly resembles the distinction of the rights (claims) of God and the rights of man in Hanafi legal doctrine. The rights of man encapsulate some benefits which are under his exclusive authority. They are related to civil law (muʿamalāt) and some aspects of penal law, such as the right of retaliation (qis ās). On the other hand, the rights of God, which resemble public law, are the rights not related exclusively to any one person but to the benefit of all humanity. By means of this distinction between the rights of man and rights of God, Islamic law is divided into two separate areas similar to the division between (Western) Public and Private law. Yet these two branches of law differ from one another in certain aspects. We observe that the area of rights of man (private law) is shaped around the concept of “milk” which is the most significant term indicating exclusivity on a property. The rights in marriage and retaliation (qisās) are also explained under the light of this term. Moreover, we can say that fiqh gives a more extensive place and time to private law, and that the main theories of fiqh are always developed in the field of private law.
İslam hukukunda, kamu hukuku- özel hukuku ayırımının temelleri ve bunun etkisi.
Keywords: Din Bilimi